Self-assembly of MoO3-decorated carbon nanofiber interlayers for high-performance lithium–sulfur batteries. Issue 4 (8th January 2020) - Li, Huilan; Wang, Xiaofei; Qi, Chu; Zhao, Chengcheng; Fu, Cuimei; Wang, Lina; Liu, Tianxi
Abstract : A self-assembled MoO3 -decorated carbon nanofiber interlayer is effectively integrated into the Li–S battery with high performance. Abstract : Lithium–sulfur (Li–S) batteries are attractive for next-generation energy storage systems due to their high theoretical capacity and energy density. However, the undesired shuttling of soluble lithium polysulfides (Li2 S n, 2 < n ≤ 8) and the uncontrolled growth of lithium dendrites have hindered their practical applications. Herein, a self-assembled freestanding MoO3 /carbon nanofiber (MoO3 /CNF) composite membrane is effectively integrated into Li–S batteries as a functional interlayer. Improved cell performance is achieved due to the strong interfacial chemical and physical interactions between the interlayers with Li2 S n . The Li–S batteries exhibit a decent cyclic stability with a fading rate of 0.12% per cycle for 500 cycles at 1675 mA g −1, a high rate performance and a low self-discharge rate. In this rational design, the CNF network provides abundant electron pathways and physically prevents polysulfide diffusion. The polar MoO3 nanorods act as effective anchoring sites by the chemical interactions with Li2 S n . Meanwhile, the suppressed Li-dendrite growth on the Li-anode surface results in a stable Li stripping/plating.